2017
DOI: 10.1155/2017/8450496
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Intestine Microbiota and Lung Health in Children

Abstract: The gastrointestinal microbiota plays a critical role in nutritional, metabolic, and immune functions in infants and young children and has implications for future lung health status. Understanding the role of intestinal dysbiosis in chronic lung disease progression will provide opportunities to design early interventions to improve the course of the disease. Gut microbiota is established within the first 1 to 3 years of life and remains relatively stable throughout the life span. In this review, we report the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 43 publications
0
34
0
1
Order By: Relevance
“…The gut microbiome in infancy is influenced by the braingut axis and maternal and neonatal factors, including prenatal colonization, mode of delivery, antibiotics, feeding patterns, infection, and environmental exposure (family vs. NICU). 25 The varying degrees of gut dysbiosis in our patients may be due to differences in disease severity, antibiotic therapy in early life, and feeding type or amount. In this study, the results of correlation analysis suggested that patients with a higher NTISS score and those who required more supplemental oxygen therapy were associated with a higher risk of having a high proportion of AE with FA bacteria, possibly due to the suitable growth of AE and FA bacteria or the inhibition of anaerobic bacteria colonization.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The gut microbiome in infancy is influenced by the braingut axis and maternal and neonatal factors, including prenatal colonization, mode of delivery, antibiotics, feeding patterns, infection, and environmental exposure (family vs. NICU). 25 The varying degrees of gut dysbiosis in our patients may be due to differences in disease severity, antibiotic therapy in early life, and feeding type or amount. In this study, the results of correlation analysis suggested that patients with a higher NTISS score and those who required more supplemental oxygen therapy were associated with a higher risk of having a high proportion of AE with FA bacteria, possibly due to the suitable growth of AE and FA bacteria or the inhibition of anaerobic bacteria colonization.…”
Section: Discussionmentioning
confidence: 89%
“…In general, colonization of the gut microbiota is established between the ages of 1 and 3 years. 25 Previous research has indicated that Actinobacteria, Proteobacteria, Bacteroidetes, and Firmicutes are the four major phyla in the full-term neonatal intestine. 26 According to our preliminary analysis of gut flora, these four bacteria phyla were also the dominant intestinal microflora in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 By altering the presumed unstable intestinal microecology of newborns, antibiotic administration can modify the host immune responses to allergens, with subsequent asthma development as one of the negative outcomes. 17,18 Antibioticinduced early intestinal dysbiosis has been associated with greater probability of early asthma development and may lead to persistent infection. 19,20 Varon et al 21 assessed the presence of Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis in the nasopharynx of infants with respiratory tract infections before and after antibiotic treatment.…”
Section: Antibiotic Usementioning
confidence: 99%
“…24 The neonatal period is a decisive time for the development of the immune system that has a lifelong impact on an individual's health. 18 Notably, the presence of favorable microbes such as Bifidobacterium longum is associated with decreased prevalence of asthma. 18 Short chain fatty acids (SCFA) produced by the gut microbes can also influence the fate of respiratory conditions.…”
Section: Relationship Between Lung Microbiome and Intestinal Microecomentioning
confidence: 99%
“…Finally, most studies agree on recognizing dysbiosis as a risk factor associated with many pediatric diseases [21]. Lower microbial diversity in early infancy seems to lead the way for the development of allergic manifestations as asthma [22,23].…”
mentioning
confidence: 99%